PENGEMBANGAN MEDIA DIORAMA DALAM PEMBELAJARAN IPS PADA SUBTEMA MANUSIA DAN LINGKUNGAN DI KELAS V SDI NUFUAK BELU - Tafuli, Anna Trifonia; Lehan, Andriyani A. D.; Fointuna, Daniel Williams (Journal of Character and ELementary Education, 2024)
: This research was conducted based on the situation in the social studies learning process which is ineffective and efficient. This study aims to develop diorama media that are relevant to social studies material on the sub-themes of humans and the environment in class V that are valid, practical and effective. Type research using development research with the ADDIE Model, which consists of 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. Collection of research data using questionnaires and tests. The research subjects were fifth-grade students of SDI Nufuak Belu as many as 25 students. The data collected consists of expert validation data, response questionnaire data from teachers and students, and test result data. The results showed that the development of diorama media for social studies learning sub-themes of humans and the environment class V SDI Nufuak Belu has very good qualifications with an achievement rate of 90.41%. Achievement of this quality is obtained from the calculation of the average media validity rate of 90.83% with a very valid, practicality rate of 96.40% with very practical, and the effectiveness rate is 84% very high